2022
DOI: 10.1017/jsi.2022.1
|View full text |Cite
|
Sign up to set email alerts
|

Education-Centred Formal Wraparound Services in Support of School-Aged Students With Complex Support Needs: A Systematic Review

Abstract: The aim of this systematic review was to map the peer-reviewed literature (2009–2019) relating to school involvement with wraparound models in the support of students with complex needs. Specific research questions addressed explored the evidence base of the efficacy of wraparound with these students and barriers and enablers in the provision of wraparound services. Database searches were conducted and a total of 50 articles were identified. The analysis revealed eight different aspects of wraparound efficacy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The authors employed a qualitative research design to gain an in-depth understanding of the experiences and perceptions of the stakeholders involved in wraparound support in regional NSW schools (Bengtsson, 2016). Principals, deputy principals, head teachers, specialist teachers, classroom teachers, and school counsellors were interviewed separately and in small groups, using a semi-structured interview protocol that was developed based on a critical review of literature focussed on wraparound models and their implementation (Cumming et al, 2022 ). The interviews were audio-recorded with the participants’ permission, transcribed verbatim, and analysed using a qualitative thematic analysis approach (Braun & Clarke, 2006 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors employed a qualitative research design to gain an in-depth understanding of the experiences and perceptions of the stakeholders involved in wraparound support in regional NSW schools (Bengtsson, 2016). Principals, deputy principals, head teachers, specialist teachers, classroom teachers, and school counsellors were interviewed separately and in small groups, using a semi-structured interview protocol that was developed based on a critical review of literature focussed on wraparound models and their implementation (Cumming et al, 2022 ). The interviews were audio-recorded with the participants’ permission, transcribed verbatim, and analysed using a qualitative thematic analysis approach (Braun & Clarke, 2006 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, wraparound coordination was shared amongst several staff members in each of the participating schools, with external providers also contributing. The claim from participants that funding for a dedicated school-based case manager would greatly enhance the effectiveness of wraparound services is strongly supported by a review of literature conducted by Cumming et al ( 2022 ), who identified sufficient funding as a major enabler of effective wraparound programs. Teams should be sufficiently funded to allow the investigation of all possible avenues of support and the development of strong working relationships with external collaborators.…”
Section: Recommendationsmentioning
confidence: 99%
“…The significance of the neighborhood unit's interrelated elements is best determined by the relation of school and the neighborhood of which it is a part (Jill et al [44,45]). The relation is exemplified by the notion of the services school (Khadduri et al [14,48]; Jill et al [14]; Cumming et al [49]; Pesch [46]; Horn [50]; Jordan et al [51]. Pesch [46] highlights the role of public schools as active participants in holistic planning for urban revitalization.…”
Section: The Impactful Neighborhood Unit Elements: What Do We Know? 2...mentioning
confidence: 99%
“…Such alliances could include representatives from various systems of care that are based in a school setting to reduce access, stigma, transportation, cost, and other concerns (Lewallen et al, 2015). These alliances would review longstanding absenteeism cases, incubate family-school-community partnerships to boost wraparound care, and institute necessary case management and accommodation practices to address salient learning, health, and behavioral issues that interfere with school attendance (Cumming et al, 2022). These alliances can be linked as well to school-based teams that utilize attendance data as an early warning signal for multiple issues (next section).…”
Section: Integrating Systems Of Carementioning
confidence: 99%